Bóg a stworzenie w teologii katolickiej - Mieczysław Ozorowski (Nicolaus Copernicus University in Toruń, 2011)
The scientific studies of the creation of the world and of man are of primary significance since they concern the very foundations of human life and give the responses to the basic questions of the sense and purpose of human life. The world was created by the Word of God. The work of creation is attributed to God the Father but all the persons of the Holy Trinity share it. The world was created by love which is God himself and who wills to share it with all the creation. The purpose of creation is the participation in the Glory of God. God is omnipotent and creates the world ex nihilo together with time and in time. God cares and provides for all his creation, even though it has been corrupted by evil and sin. Man, who was made in the image and likeness of God, is the summit of the Creator's work. As male and female, people are obliged, in the name of God and according to his principles and laws, to care for the world which they have been entrusted with.